The interaction among gut microbes, the intestinal barrier and short chain fatty acids - Ma, Jiayu; Piao, Xiangshu; Mahfuz, Shad; Long, Shenfei; Wang, Jian (Animal Nutrition, 2022)
The mammalian gut is inhabited by a massive and complicated microbial community, in which the host achieves a stable symbiotic environment through the interdependence, coordination, reciprocal constraints and participation in an immune response. The interaction between the host gut and the microbiota is essential for maintaining and achieving the homeostasis of the organism. Consequently, gut homeostasis is pivotal in safeguarding the growth and development and potential productive performance of the host. As metabolites of microorganisms, short chain fatty acids are not only the preferred energy metabolic feedstock for host intestinal epithelial cells, but also exert vital effects on antioxidants and the regulation of intestinal community homeostasis. Herein, we summarize the effects of intestinal microorganisms on the host gut and the mechanisms of action of short chain fatty acids on the four intestinal barriers of the organism, which will shed light on the manipulation of the intestinal community to achieve precise nutrition for specific individuals and provide a novel perspective for the prevention and treatment of diseases.